High-entropy alloy / LIG composite material and preparation method and application thereof
By synthesizing high-entropy alloy magnetic nanoparticles in three-dimensional porous graphene, and using laser induction and Joule hot flash evaporation technology, a high-entropy alloy/LIG composite material was prepared, which solved the problem of high density and poor stability of existing electromagnetic wave absorption materials, and achieved the effect of maintaining good wave absorption performance in harsh environments.
Patent Information
- Application Number
- CN202411891043.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
While meeting the requirements of thin, light, wide and strong, existing electromagnetic wave absorbing materials have problems such as high density, poor stability, complex preparation process and decay of wave absorbing properties in high temperature or strong corrosive environments.
By synthesizing high-entropy alloy magnetic nanoparticles with good dispersion in situ in three-dimensional porous graphene, a high-entropy alloy/LIG composite material was prepared by using laser induction and Joule thermal flash evaporation technology to enhance its electromagnetic wave absorption performance.
This material broadens the absorption bandwidth under the condition of ensuring absorption strength, reduces the overall density of the material, improves electromagnetic wave absorption performance, and maintains good wave absorption performance in harsh environments.
Smart Images

Figure CN119753579A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electromagnetic absorbing materials, and in particular to a high entropy alloy / LIG composite material and a preparation method and application thereof. Background Art
[0002] The continuous development of 5G technology has made more and more electronic devices that use electromagnetic waves as information carriers widely used in people's production and life. In practical applications, electromagnetic wave absorbing materials must meet the characteristics of "thin, light, wide, and strong", that is, thin thickness, low density, wide bandwidth, and high reflection loss.
[0003] At present, electromagnetic wave absorbing materials can be divided into two categories according to their working mechanism: electric loss materials and magnetic loss materials. Electric loss materials such as carbon fiber, carbon nanotubes, graphene, etc. have strong absorption strength and light density, but often have low impedance levels and can only absorb electromagnetic waves of one or several frequencies. Magnetic loss materials such as iron oxides, magnetic metal nanomaterials, carbonyl iron, etc. have good ability to absorb electromagnetic radiation and can achieve strong absorption at low frequencies, but the material has defects such as high density, poor stability, and complex preparation process. In addition, the absorption performance of traditional magnetic absorbing materials will decline in harsh environments with high temperatures or strong corrosion, and due to the influence of the Snoek limit, its magnetic permeability will drop sharply at high frequencies, resulting in a decrease in impedance matching, which is not conducive to electromagnetic wave absorption. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a high entropy alloy / LIG composite material, in which high entropy alloy magnetic nanoparticles with good dispersion are in situ synthesized in three-dimensional porous graphene by laser induction and Joule thermal flash evaporation technology, and the composite of laser-induced three-dimensional porous graphene and high entropy alloy enables the material to have good physical and chemical properties, enhances the electromagnetic wave absorption performance of the composite material, and can broaden the absorption bandwidth while ensuring the absorption intensity, thereby reducing the overall density of the material.
[0005] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0006] One of the objects of the present invention is to provide a method for preparing a high entropy alloy / LIG composite material, comprising the following steps:
[0007] (1) mixing a metal precursor and an organic carbon source in the form of a solution and then curing the mixture into a film;
[0008] (2) subjecting the thin film obtained in step (1) to laser irradiation to obtain a metal nanoparticle / LIG composite material;
[0009] (3) Performing Joule thermal flash evaporation on the metal nanoparticle / LIG composite material obtained in step (2) to obtain a high entropy alloy / LIG composite material.
[0010] A second object of the present invention is to provide a high entropy alloy / LIG composite material prepared by the above-mentioned method for preparing the high entropy alloy / LIG composite material.
[0011] A third object of the present invention is to provide the use of the high entropy alloy / LIG composite material as an electromagnetic absorbing material.
[0012] Laser-induced graphene (LIG) has a three-dimensional porous structure, high crystallinity and large specific surface area, which can effectively absorb electromagnetic waves and achieve lightweight design while meeting excellent wave-absorbing performance.
[0013] Joule flash evaporation technology generates huge Joule heat by applying current at both ends of the conductor, which shortens the heat treatment time to seconds. It can effectively control the composition and microstructure of high-entropy alloys, thereby inducing a uniform mixing of the alloy components. The Joule flash evaporation process may optimize the electronic structure inside the high-entropy alloy, thereby improving the electromagnetic wave absorption performance of the composite material.
[0014] The beneficial effects of the present invention are as follows: LIG in the composite material of the present invention is conducive to multiple refraction and scattering of electromagnetic waves, the composite of LIG and high entropy alloy is conducive to reducing the overall density of the composite material, and the porous structure of LIG can increase the surface area of the composite material; the high entropy effect of the high entropy alloy can increase the polarization loss of the composite material, and the lattice distortion effect can enhance the electron scattering inside the material, thereby increasing the electromagnetic wave absorption performance of the composite material. In addition, the present invention quickly prepares the high entropy alloy / graphene composite material by combining laser induction technology and Joule thermal flash evaporation technology, which greatly shortens the preparation cycle and provides a new way to prepare the high entropy alloy / graphene composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a scanning electron microscope image of the composite material prepared in Example 1;
[0016] Figure 2 X-ray diffraction patterns of the composite materials prepared in Examples 1 to 5;
[0017] Figure 3 The wave absorbing performance of the wave absorbing ring prepared in Example 1;
[0018] Figure 4 The absorbing performance of the absorbing ring prepared in Example 16. DETAILED DESCRIPTION
[0019] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0020] The present invention provides a method for preparing a high entropy alloy / LIG composite material, comprising the following steps:
[0021] (1) mixing a metal precursor and an organic carbon source in the form of a solution and then curing the mixture into a film;
[0022] (2) subjecting the thin film obtained in step (1) to laser irradiation to obtain a metal nanoparticle / LIG composite material;
[0023] (3) Performing Joule thermal flash evaporation on the metal nanoparticle / LIG composite material obtained in step (2) to obtain a high entropy alloy / LIG composite material.
[0024] In the present invention, the metal precursor is a hydrochloride, sulfate, nitrate or oxide of iron, cobalt, nickel, copper or manganese.
[0025] For magnetic loss type materials, the present invention selects FeCoNiCuMn high entropy alloy. The five elements of Fe, Co, Ni, Cu and Mn are in the same period and have the same electronic layer structure, similar chemical properties and relative atomic mass, which supports the formation of high entropy alloy. The FeCoNi-based high entropy alloy has high saturation magnetization, high magnetic permeability and good wave absorption performance, and the addition of Cu element can affect the physical properties, corrosion resistance and high temperature oxidation resistance of high entropy alloy materials; the addition of Mn element can change the magnetic moment of high entropy alloy materials, thereby improving the magnetic properties.
[0026] In the present invention, the organic carbon source is a synthetic polymer and / or a natural polymer. Further, the synthetic polymer includes but is not limited to at least one of polyimide, polyethersulfone, polyethylene terephthalate, polystyrene, phenolic resin, and polyamic acid; the natural polymer includes but is not limited to at least one of lignin, cellulose, starch, polysaccharide, chitosan, chitin, and derivatives thereof.
[0027] In step (1), the metal precursor and the organic carbon source are uniformly mixed in the form of a solution and then allowed to stand before solidifying into a film. The purpose of standing is to discharge bubbles in the mixed solution.
[0028] In the present invention, the molar ratio of iron, cobalt, nickel, copper and manganese in the metal precursor is (1-5):(1-5):(1-5):(1-5):(1-5).
[0029] In the present invention, the light source of the laser is at least one of a solid-state laser, a semiconductor laser, a fiber laser, and a gas laser.
[0030] In the present invention, the laser wavelength of the laser irradiation is 100nm-20μm, the laser scanning rate is 1-500mm / s, the laser power is 0.1-100W, and the pulse frequency is 1-1000KHz.
[0031] In the present invention, the Joule heat flash evaporation is carried out in a vacuum atmosphere, the Joule heat voltage is 80 to 150 V, the flash discharge time is 1 to 10 s, and the temperature is 2500 to 3500° C.
[0032] The present invention provides a high entropy alloy / LIG composite material prepared by the above-mentioned preparation method of the high entropy alloy / LIG composite material.
[0033] The present invention also provides use of the high entropy alloy / LIG composite material as an electromagnetic wave absorbing material.
[0034] Example 1
[0035] Iron nitrate, cobalt nitrate, nickel nitrate, copper nitrate, and manganese nitrate were added to N,N dimethylacetamide (DMAC) in a molar ratio of 1:1:1:1:1 of Fe, Co, Ni, Cu, and Mn to prepare a metal salt solution with a concentration of 3 mmol / L. Thermoplastic polyimide and DMAC were mixed evenly in a volume ratio of 2.5:1 to prepare a polymer solution with a solid content of 30%. The metal salt solution and the polymer solution were mixed evenly in a culture dish in a volume ratio of 1:2, and placed in a vacuum oven after standing overnight, and heated to 180°C at a heating rate of 5°C / min for insulation. The cured film was taken out, fixed to a steel plate with a high-temperature resistant tape, and irradiated with a CO2 laser with a laser wavelength of 10.6μm, a laser scanning rate of 90mm / s, a laser power of 5.8W, and a pulse frequency of 5KHz to obtain a metal nanoparticle / LIG composite material. The metal nanoparticle / LIG composite material was subjected to Joule thermal flash evaporation in a vacuum atmosphere, with a Joule thermal voltage of 80 V, a flash discharge time of 1 s, and a temperature of 2580° C. to obtain a composite material (abbreviated as LIG / FeCoNiCuMn).
[0036] Figure 1 This is a scanning electron microscope image of the composite material prepared in Example 1. Figure 1 It can be seen that the metal nanoparticles are loaded in the three-dimensional porous structure of graphene, are spherical in shape and are relatively evenly distributed.
[0037] The composite material prepared above was mixed with paraffin wax at a mass ratio of 30:70 and heated to 120°C to make an absorbing ring (concentric rings). The electromagnetic parameters of the absorbing ring in the frequency range of 2 to 18 GHz were tested by a vector network analyzer. The absorbing performance of the absorbing ring was evaluated by simulation calculation based on the transmission line theory, combining the maximum reflection loss and the maximum effective absorption frequency bandwidth.
[0038] Embodiments 2 to 5
[0039] The method of Example 1 was followed except that the molar ratio of Fe, Co, Ni, Cu, and Mn was adjusted to obtain LIG / FeCoNiCu x Mn 1-x .
[0040] Table 1
[0041] Composite Materials XRD test results Example 1 LIG / FeCoNiCuMn Figure 2 Example 2 <![CDATA[LIG / FeCoNiCu 0.2 Mn 0.8 ]]> Figure 2 Example 3 <![CDATA[LIG / FeCoNiCu 0.4 Mn 0.6 ]]> Figure 2 Example 4 <![CDATA[LIG / FeCoNiCu 0.6 Mn 0.4 ]]> Figure 2 Example 5 <![CDATA[LIG / FeCoNiCu 0.8 Mn 0.2 ]]> Figure 2
[0042] from Figure 2 It can be seen that when the molar ratio of Fe, Co, Ni, Cu, and Mn elements is 1:1:1:1:1, the alloy diffraction peak of the composite material is more obvious, indicating that the crystallinity of the composite material is higher at this time.
[0043] Embodiments 6 to 19
[0044] The method of Example 1 is followed, except that the concentration of the metal salt solution or the mass ratio of the composite material to the paraffin is adjusted, as shown in Table 2.
[0045] Table 2
[0046]
[0047]
[0048] It can be seen from Table 2 that changing the concentration of the metal salt solution or the mass ratio of the composite material to the paraffin wax will affect the microwave absorbing performance of the composite material.
[0049] from Figure 3 It can be seen that when the absorbing ring prepared in Example 1 has a thickness of 3.4 mm, the minimum reflection loss is -41.2 dB, and the maximum effective absorption (reflection loss is less than -10 dB) frequency bandwidth can reach 5.05 GHz.
[0050] from Figure 4 It can be seen that when the absorbing ring prepared in Example 16 has a thickness of 7.3 mm, the minimum reflection loss is -62.23 dB, and the maximum effective absorption (reflection loss is less than -10 dB) frequency bandwidth can reach 1.67 GHz.
[0051] Embodiment 20
[0052] The method of Example 1 was followed, except that the laser irradiation conditions were adjusted, the laser wavelength was 10.6 μm, the laser scanning rate was 100 mm / s, the laser power was 50 W, and the pulse frequency was 10 KHz.
[0053] When the thickness of the absorbing ring prepared in Example 20 is 10 mm, the minimum reflection loss is -37.30 dB, and the effective absorption frequency bandwidth reaches 1.1 GHz.
[0054] Embodiment 21
[0055] The method of Example 1 was followed, except that the laser irradiation conditions were adjusted, the laser wavelength was 10.6 μm, the laser scanning rate was 200 mm / s, the laser power was 100 W, and the pulse frequency was 20 KHz.
[0056] When the thickness of the absorbing ring prepared in Example 21 is 1.6 mm, the minimum reflection loss is -5.48 dB, and the effective absorption frequency bandwidth is 0.
[0057] Embodiment 22
[0058] The method of Example 1 was followed, except that the Joule thermal flash evaporation conditions were adjusted, the Joule thermal voltage was 100 V, the flash evaporation discharge time was 1 s, and the temperature was 2840°C.
[0059] When the thickness of the absorbing ring prepared in Example 22 is 1.3 mm, the minimum reflection loss is -5.84 dB and the effective absorption frequency bandwidth is 0.
[0060] Embodiment 23
[0061] The method of Example 1 was followed, except that the Joule thermal flash evaporation conditions were adjusted, the Joule thermal voltage was 150 V, the flash evaporation discharge time was 2 s, and the temperature was 3020°C.
[0062] When the thickness of the absorbing ring prepared in Example 23 is 2.4 mm, the minimum reflection loss is -4.88 dB and the effective absorption frequency bandwidth is 0.
[0063] Comparative Example 1
[0064] The method of Example 1 is followed, except that pure graphene is used instead of the metal nanoparticle / LIG composite material to be composited with paraffin to prepare the absorbing ring.
[0065] When the thickness of the absorbing ring prepared in Comparative Example 1 is 1.2 mm, the minimum reflection loss is -8.74 dB and the effective absorption bandwidth is 0.
[0066] Comparative Example 2
[0067] According to the method of patent CN 115161531 A.
[0068] When the thickness of the absorbing ring prepared in Comparative Example 2 is 2.5 mm, the minimum reflection loss is -42.5 dB; when the thickness is 2 mm, the maximum effective absorption bandwidth can reach 4.9 GHz.
[0069] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a high entropy alloy / LIG composite material, characterized in that: The following steps are involved: (1) mixing a metal precursor and an organic carbon source in the form of a solution and then curing the mixture into a film; (2) subjecting the thin film obtained in step (1) to laser irradiation to obtain a metal nanoparticle / LIG composite material; (3) Performing Joule thermal flash evaporation on the metal nanoparticle / LIG composite material obtained in step (2) to obtain a high entropy alloy / LIG composite material.
2. The preparation method according to claim 1, characterized in that: The metal precursor is a hydrochloride, sulfate, nitrate or oxide of iron, cobalt, nickel, copper or manganese.
3. The preparation method according to claim 1, characterized in that: The organic carbon source is a synthetic polymer and / or a natural polymer.
4. The preparation method according to claim 3, characterized in that: The synthetic polymer is selected from at least one of polyimide, polyethersulfone, polyethylene terephthalate, polystyrene, phenolic resin and polyamic acid; the natural polymer is selected from at least one of lignin, cellulose, starch, polysaccharide, chitosan, chitin and derivatives thereof.
5. The preparation method according to claim 1, characterized in that: The molar ratio of iron, cobalt, nickel, copper and manganese in the metal precursor is (1-5):(1-5):(1-5):(1-5):(1-5):(1-5).
6. The preparation method according to claim 1, characterized in that: The laser light source is at least one of a solid-state laser, a semiconductor laser, a fiber laser, and a gas laser.
7. The preparation method according to claim 1, characterized in that: The laser wavelength of the laser irradiation is 100nm-20μm, the laser scanning rate is 1-500mm / s, the laser power is 0.1-100W, and the pulse frequency is 1-1000KHz.
8. The preparation method according to claim 1, characterized in that: The Joule heat flash evaporation is carried out in a vacuum atmosphere, the Joule heat voltage is 80-150V, the flash discharge time is 1-10s, and the temperature is 2500-3500°C.
9. A high entropy alloy / LIG composite material prepared by the method for preparing a high entropy alloy / LIG composite material according to any one of claims 1 to 8.
10. Use of the high entropy alloy / LIG composite material according to claim 9 as an electromagnetic absorbing material.